The Effect Of Yoga Exercises On Dysmenorrhea Pain In Female Adolescents Of Hasyim Asyari Junior High School, Ngawonggo Village, Tajinan District, Malang Regency - Putri Eka Sejati; Marina Islami Putri; Reni Yuli Astutik; Shanty Natalia (Master of Public Health Program Universitas STRADA Indonesia, 2026)
During menstruation, adolescent girls commonly experience dysmenorrhea. This study aimed to determine the effect of yoga practice on dysmenorrhea pain in female students at Hasyim Asyari Junior High School in Ngawonggo Village, Tajinan District, Malang Regency. The study used a quasi-experimental design with a single pretest-posttest group. The study sample consisted of 34 adolescent girls who experienced menstrual pain and met the inclusion criteria. The results showed substantial changes in pain levels before and after the yoga intervention. During the pretest, no participants reported pain (0%), but this increased to 3 students (8.8%) after the intervention. Mild pain increased from 0% to 20 students (58.8%). Moderate pain decreased from 12 students (35.3%) to 10 students (14.7%). Severe pain decreased significantly from 19 students (55.9%) to 1 student (2.9%). In conclusion, yoga practice significantly reduced dysmenorrhea pain in adolescent girls at Hasyim Asyari Junior High School. These findings highlight the importance of health workers providing education on menstrual pain management and collaborating with school health workers (UKS) to promote prevention strategies, such as incorporating yoga exercise programs for young female students.